Avaliação de um (re) caminho em busca da melhoria do ensino médio: a experiência da Escola de Ensino Médio em Tempo Integral (EEMTI) Custódio da Silva Lemos, Distrito de Guanacés, em Cascavel-Ceará - Alves, André Luiz Farias (2022)
Full-time High School is experienced in the State of Ceará, and its implementation is justified by the need to expand opportunities for comprehensive training of young people from Ceará, improving the educational service offered in state schools and improving the educational quality of state public high schools. Therefore, this work has the general objective of evaluating the effects of Full-Time Education (ETI) in the propaedeutic high school Custódio da Silva Lemos, from the context and the educational and social trajectory of the students. In this perspective, we will conduct an investigation of the educational public policies of Ceará, between the years 2016 and 2022, and the study has as reference the perspective of an in-depth evaluation as a proposal capable of subsidizing the broad understanding of the constructions that permeate in the relationships that revolve around the evaluation of a public policy, allowing it a comprehensive and experiential analysis. We demarcate an exploratory study, of qualitative and quantitative approach to be carried out in the Full-Time High School Custódio da Silva Lemos, located in the district of Guanacés in the city of Cascavel, Ceará, and this choice occurred because the institution was one of the first schools in the state of Ceará (2016) to experience the change in curricular supply, i.e., from partial high school mode to regular full high school mode. In this case study, we followed the methodological path of the research based on the legal order and on the school results obtained by the students when they finished the Full-Time High School; in addition to records of observations in the field school and the application of focus groups, from a semi-structured script, contemplating school managers, teachers, and students. Therefore, we understand that the EEMTIs were created to meet goal 6 of the PNE, aiming to improve student performance in relation to school flow, proficiency, and equity of results. In addition, these institutions seek to develop the comprehensive training of students, which we evidenced by the evolution of the educational data of EEMTI Custódio da Silva Lemos (in particular, between the years 2013 to 2019).